Career Hunters: Business Analysis and Implementation of Training Programs for The Companies and Job-Seeking Customers. - Salem Alazmi; Yousef Rouhaldeen; Abdulaziz Alsarraf; Anindya Septisuwendani; Stefany Yulieth Taborda Henao (Journal of the Community Development in Asia (JCDA), 2019)
For the Nusantara Project it has been decided to look for a company who provides and connects people with companies. This company is Career Hunters Kuwait. The company is helping different organizations in recruitment matters, mostly, its Mission is to provide the highest quality tailored services in all stages of the recruitment process with an emphasis on customized consultancy services for the recruitment of staff in all disciplines, at all levels, both permanent and temporary” (Career Hunters Kuwait, 2018). The company seeks to connect the most talented employees with different organizations according to their demand. It collects data from previous companies and investigate about the specifications and the employer requirements and then sets on finding the perfect candidate according with these requirements. Although it has been offering important services for the customers, there is a new idea brewing for this organization. This idea it’s about proving training facilities, along with the recruitment facilities for the organizations. It has been analyzed that there is a need on the companies for trained employees as it has been hiring employees from all over the world according to the required talent. Training is a crucial need for the organizations to have focus on. The benefits that Career Hunters will achieve with the implementation of this new service lay on the capacity of the company to provide highly talented employees for the companies according with their needs and will charge fees, which it also comes from the demanding professionals of its clients. It can also offer these services at an international level. In this investigation, there is a finished talk about the objective market for this new idea in the business and there will be an examination of financial, social, political and natural impacts of this new business idea. As per the innovative condition, it is examined in this investigation that these are additionally positive as the enrollment needs in Kuwait are extraordinary. With this uncharted territory there are variables and risks that need to be addressed; dangers such as: it incorporates the risk for disappointment and the low agreeableness on the client side, reluctancy to pay a higher fee only for trained candidates. There is a hazard of losing a tremendous amount of capital which is an extraordinary misfortune to the organization. This idea is reasonable as it is in the interest of the clients, there will be a expand fascination as the clients don't have to go and try to find a new company to do the training for their future employees, because that service will be included in the Career Hunters contract.